TINJAUAN HUKUM TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 88/PUU-XIV/2016 - Imam Sumantri (Legal Spirit, 2019)
Yogyakarta, pinned to the Special Region because it has its own historical factors from other regions, so that Yogyakarta has specificities that are given the law through Law No. 13 of 2012 concerning Yogyakarta Regional Privileges. On his journey there seemed to be a problem, with the Sultan currently not having a son. This study discusses: First, What is the ratio decidendi (judge's consideration) of the Constitutional Court Decision 88 / PUU-XIV / 2016 in interpreting article 18B of the 1945 Constitution? Second, how is the examination of the Constitutional Court Decision 88 / PUU-XIV / 2016, and the reformulation of regulations. This research uses normative legal research, the method of approach used is the statutory regulation, conceptual approach, historical approach and philosophy. The results of the study show that, first, there is no definite benchmark by the Constitutional Court in interpreting Article 18B of the 1945 Law concerning asymenteric decentralization. Thus, this makes the Constitutional Court Decision 88 / PUU-XIV / 2016, in its consideration, inconsistencies occur. Second, the examination of the verdict, more specifically on the legal standing, where the loss is not felt by the applicant. In the future reformulation, the state does not need to intervene in the internal affairs of the palace, either through court rulings or legislative regulations.Key words: Legal Review, MK Decision, Special Region of Yogyakarta, Asimeteris Decentralization